2019
DOI: 10.2174/1381612825666190306163310
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid Receptor Antagonists in Essential and Resistant Hypertension

Abstract: Background: Mineralocorticoid receptor antagonists are a second-line class of antihypertensive drugs, which have been accounted for as the optimal add-on therapy in the triple algorithm for the management of resistant hypertension. Objectives: To assess the effects of mineralocorticoid receptor antagonists in the treatment of patients with essential hypertension and resistant hypertension. Method: We conducted a meticulous review of the literature and comprehensive identification of the clinical trials as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 105 publications
0
5
0
Order By: Relevance
“…Together, mineralocorticoid receptor antagonists have opened a novel therapeutic window for the management of patients with secondary/ resistant hypertension (Faulkner & Belin de Chantemèle, 2019;Imprialos et al, 2018;Sato, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, mineralocorticoid receptor antagonists have opened a novel therapeutic window for the management of patients with secondary/ resistant hypertension (Faulkner & Belin de Chantemèle, 2019;Imprialos et al, 2018;Sato, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, patients suffering from primary aldosteronism have an increased propensity to develop cardiovascular disease conditions and target organ damage (Stavropoulos et al., 2018). Together, mineralocorticoid receptor antagonists have opened a novel therapeutic window for the management of patients with secondary/ resistant hypertension (Faulkner & Belin de Chantemèle, 2019; Imprialos et al., 2018; Sato, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Mineralocorticoid receptor antagonists are potassium‐sparing diuretics, and these are clinically employed in the management of congestive heart failure [3]. However, studies have shown their expanding spectrum in a number of diseases including diabetic nephropathy [5], treatment‐resistant hypertension [6]. There have been studies showing that activation of mineralocorticoid receptors may be associated with impairment in memory [16], and blockade of these receptors may be beneficial in memory [17].…”
Section: Discussionmentioning
confidence: 99%
“…In clinics, these are predominantly used for the management of congestive heart failure and these have been reported to reduce cardiac remodeling and mortality rate in these patients [3]. Studies have shown their potential in modifying the pathogenesis of diseases including diabetic cardiomyopathy [4], diabetic nephropathy [5], treatment‐resistant hypertension [6], inflammasome formation [7], vascular dysfunction [8], and muscular dystrophy [9].…”
Section: Introductionmentioning
confidence: 99%
“…Aldosterone exacerbates hypertension by promoting sodium reabsorption in distal nephrons by increasing the number and opening frequency of epithelium sodium channels, thereby leading to volume expansion. Additionally, aldosterone damages various target organs, including vessels, kidneys, and the heart, via multiple mechanisms, such as upregulation of connective tissue growth factor and subsequent fibrosis; production of proinflammatory molecules contributing to organ and extracellular matrix remodeling; oxidative stress; and stimulation of cell migration, proliferation, and apoptosis [28]. Moreover, target organ damage may worsen hypertension.…”
Section: Phase II Trial Of the Aldosterone Synthase Inhibitor Baxdros...mentioning
confidence: 99%